2020
DOI: 10.48550/arxiv.2011.03629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulsating hydrogen-deficient white dwarfs and pre-white dwarfs observed with TESS: I. Asteroseismology of the GW Vir stars RX J2117+3412, HS 2324+3944, NGC 6905, NGC 1501, NGC 2371, and K 1-16

Alejandro H. Córsico,
Murat Uzundag,
S. O. Kepler
et al.

Abstract: Pulsating hydrogen-deficient white dwarfs and pre-white dwarfs observed with TESS

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(122 reference statements)
1
1
0
Order By: Relevance
“…What remains to be discussed is the cause of the photometric variability and how it is linked to the occurrence of the UHE features and He II line problem. The photometric periods of all stars in our sample are well above the theoretical upper limit of 10 4 s predicted for non-radial gmode pulsations that are frequently observed amongst PG 1159 stars (most of them having periods below 3000 s, Quirion et al 2007;Córsico et al 2019Córsico et al , 2020. Thus, we see two possible scenarios that could instead account for the photometric variability in our stars -one is linked to close binaries, and the other one related to magnetic fields.…”
Section: Discussionsupporting
confidence: 69%
“…What remains to be discussed is the cause of the photometric variability and how it is linked to the occurrence of the UHE features and He II line problem. The photometric periods of all stars in our sample are well above the theoretical upper limit of 10 4 s predicted for non-radial gmode pulsations that are frequently observed amongst PG 1159 stars (most of them having periods below 3000 s, Quirion et al 2007;Córsico et al 2019Córsico et al , 2020. Thus, we see two possible scenarios that could instead account for the photometric variability in our stars -one is linked to close binaries, and the other one related to magnetic fields.…”
Section: Discussionsupporting
confidence: 69%
“…From the continuous light curves produced by the space missions such as Kepler and K2 and now TESS, it has been observed that oscillation frequencies in compact stars, including pulsating sdB stars, DBV and DOV pulsating white dwarfs, may not be stable (Silvotti et al 2019;Zong et al 2016b;Córsico et al 2020). It is known that the frequency and amplitude variations mostly occur due to beatings of unresolved peaks or unresolved multiplets.…”
Section: Frequency and Amplitude Variationsmentioning
confidence: 99%